Inquiry‐Based Stress Reduction Meditation Technique for Teacher Burnout:A Qualitative Study. Issue 2 (29th March 2017) - Schnaider‐Levi, Lia; Mitnik, Inbal; Zafrani, Keren; Goldman, Zehavit; Lev‐Ari, Shahar
ABSTRACT: An inquiry‐based intervention has been found to have a positive effect on burnout and mental well‐being parameters among teachers. The aim of the current study was to qualitatively evaluate the effect of the inquiry‐based stress reduction (IBSR) meditation technique on the participants. Semi‐structured interviews were conducted before and after the IBSR intervention and were analyzed using the interpretative phenomenological analysis method. Before the intervention, the teachers described emotional overload caused by two main reasons: (1) multiple stressful interactions with students, parents, colleagues, and the educational system, and (2) the ideological load of their profession—trying to fulfill high expectations of performance and the manifesting educational values. Following the intervention, the teachers described a sense of centeredness and a greater ability to accept reality. They reported improvements in setting boundaries, thought flexibility, and self‐awareness. These improvements assisted them in coping with the complex and dynamic nature of their profession. These positive effects suggest that IBSR is an effective technique in reducing teachers' burnout and promoting mental well‐being.